2019
DOI: 10.1016/j.fitote.2019.104274
|View full text |Cite
|
Sign up to set email alerts
|

Lichen butyrolactone derivatives disrupt oral bacterial membrane

Abstract: We have previously demonstrated that out of the butyrolactones series synthesized based on the natural lichen metabolite lichesterinic acid, compound (B-13) was the most effective against oral bacteria. However, its antibacterial mechanism is still unknown. In this study, we have investigated its bacterial localization by synthesizing a fluorescently labeled B-13 with NBD while maintaining its antibacterial activity. We showed that this compound binds to Streptococcus gordonii cell surface, as demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Sweidan et al 61 reported that the treatment with doxycycline caused cytoplasmic alterations, as suggested by the presence of round bodies in the cytoplasm with a similar electron density as clear vesicles. The results suggested considerable damage to the Streptococcus gordonii membrane, and this membrane disruption property could be the basis of the antibacterial activity of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Sweidan et al 61 reported that the treatment with doxycycline caused cytoplasmic alterations, as suggested by the presence of round bodies in the cytoplasm with a similar electron density as clear vesicles. The results suggested considerable damage to the Streptococcus gordonii membrane, and this membrane disruption property could be the basis of the antibacterial activity of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Stacked images were collected from ten different positions on every surface. The image attainment and investigation were executed as illustrated earlier. , Images were studied, and by using COMSAT the specific biovolume (μm 3 /μm 2 ) in the biofouling layer was estimated. An image processing software83, MATLAB 6.5 (MathWorks, Inc., Natick, MA), attached with an image handling toolbox, was used for this purpose .…”
Section: Methodsmentioning
confidence: 99%
“…hyssopifolia, L. adscendes, L. leptocarpa, and L. peploides. Previous studies have shown that Ludwigia species are diverse in polyphenol compounds and have many bioactivities such as having antioxidant, antimicrobial, and anticancer properties (Wu et al, 2010;Yakob et al, 2012;Yakob et al, 2015;Smida et al, 2018;Baky et al, 2022;Shawky et al, 2023). However, the plants have not yet been studied in terms of their ability to inhibit the growth of cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%